Poly(Vinyl Alcohol) Drug and PVA–Drug–Surfactant Complex Organogel with Dimethyl Sulfoxide as a Drug Delivery System - Sabina Otarbayeva; Dmitriy Berillo (Gels)
The relevance of active research lies in the need to develop new technologies to improve drug delivery methods for the effective treatment of wound healing. Additionally, the potential application of organogels in other areas of biomedicine, such as creating medical patches with controlled drug delivery, indicates a wide range of possibilities for using this technology. This study focuses on developing controlled drug delivery systems using organogels as carriers for ceftriaxone and ofloxacin. By selecting optimal formulations, organogels were created to immobilize the drugs, facilitating their effective and sustained release. The swelling behavior of the hydrogels was studied, showing a swelling coefficient between 16 and 32%, indicating their ability to absorb liquid relative to their weight. Drug release studies demonstrated that ceftriaxone was released 1.8 times slower than ofloxacin, ensuring a more controlled delivery. Microbiological tests confirmed that the organogels containing ofloxacin exhibited antimicrobial activity against Escherichia coli, Bacillus subtilis, and Staphylococcus aureus. However, it was a challenge to estimate activity for the model antibiotic ceftriaxone due to bacterial resistance to it. Organogel poly(vinyl alcohol) (PVA)-DMSO–alginate modifications with surfactant cetylpyridinium bromide led to the formation of a polyelectrolyte complex on the interphase, allowing further enhanced the prolonged release of the drugs. The research identified that the optimal compositions for sustained drug release were organogels with compositions PVA (10%)-PVP (1%) DMSO (50%) and PVA (10%)-DMSO (50%) formulations, illustrating the transparent nature of these organogels making them suitable for ophthalmological application. Various organogels compositions (PVA-DMSO, PVA-poly(vinylpyrrolidone)-DMSO, PVA-DMSO–alginate, PVA-DMSO-PLGA, PVA-DMSO–drug–surfactant) loaded with ceftriaxone, ofloxacin, and surfactant were prepared and characterized, highlighting their potential use in antibiotic patches for wound healing. These organogels illustrate promising results for localized treatment of infections in wounds, cuts, burns, and other skin lesions.